Quo Vadis Protection of Human Rights in Coercive Confiscation Efforts - Taufik Tri Prabowo; Ade Saptomo (Cerdika: Jurnal Ilmiah Indonesia, 2024)
The protection of human rights in the context of compulsory seizure efforts remains a topic of debate in legal practice in Indonesia. Seizures are often carried out without regard for fundamental individual rights, resulting in the potential for human rights violations, particularly concerning property rights and justice. This study aims to examine how human rights protections are implemented in the seizure procedures undertaken by law enforcement officials. The research method employed is normative juridical, utilizing an approach based on statutory regulations, case studies, and legal doctrine analysis. Data collected are qualitatively analyzed through literature reviews and eval_uations of relevant cases. The findings indicate that while there are regulations governing seizure procedures, their implementation often does not align with human rights principles. There is an urgent need for improvements in oversight mechanisms and accountability in the seizure process to prevent abuse of power. This research recommends reinforcing standard operating procedures that adhere to respect for human rights and stringent oversight in every seizure action.